Does College Enrollment and Bachelor's Completion by Mothers Impact Children's Educational Outcomes?. (January 2017) - Monaghan, David
Today, many undergraduates are themselves raising children. But does college-going by parents improve their offspring's educational attainment? I address this question using data from the National Longitudinal Survey of Youth–1979 and linked Children and Young Adults Survey. I first model postnatal college enrollment and bachelor's completion by mothers and use predicted probabilities to minimize selection bias through inverse probability of treatment weighting. I then estimate the impact of maternal college enrollment and attainment on offspring's likelihood of graduating from high school, enrolling in college, and completing a four-year degree. I find sizeable effects of maternal college completion on all outcomes, but the impact of maternal enrollment without completion is considerably muted. I review implications for sociological research and policies to assist nontraditional students.